Clinical cure induced by pegylated interferon α-2b in the advantaged population of chronic hepatitis B virus infection: a retrospective cohort study - Wen, Chaojing; Wang, Yixuan; Tian, Haoyue; Lei, Yu; Wang, Zhiyi; Cai, Dachuan; Zhou, Zhi; Shi, Xiaofeng (Frontiers in Cellular and Infection Microbiology, 2024)
Background: Among the advantaged population with clinical cure of chronic hepatitis B, chronic inactive hepatitis B virus carriers (IHCs) and nucleoside analog-experienced patients have similar serological manifestations. This study established non-interferon-treated groups as control to compare the efficacy of Peg-IFNα-2b in achieving clinical cure between IHCs and NA-experienced patients. Method: Total 270 patients were enrolled in this observational study, the IHCs cohort had 55 patients received Peg-IFNα-2b (Peg-IFN group), and the other 70 patients did not receive any antiviral treatment (Untreated group). Patients treated with NAs were divided into two groups, one group (70 patients) receiving NAs add-on Peg-IFNα-2b therapy regimen (NAs add-on Peg-IFN group), and another group (75 patients) continuous NAs monotherapy (NAs group). The primary endpoints are the HBsAg clearance and HBsAg seroconversion at 48 weeks and 72 weeks. Results: At 48 weeks, 65.5% (36/55) and 52.9% (37/70) patients got HBsAg clearance in Peg-IFN group and NAs add-on Peg-IFN group (P=0.156). HBsAg seroconversion was achieved 47.3% (26/55) of Peg-IFN group, 34.3% (24/70) of NAs add-on Peg-IFN group (P=0.141). Followed up to 72 weeks, 36 patients in the Peg-IFN group achieved HBsAg loss (65.5%, 36/55), and 33 patients in the NAs addon Peg-IFN group achieved HBsAg clearance (47.1%, 33/70) which significantly higher than the Peg-IFN group (P=0.041). And the HBsAg seroconversion rates in the Peg-IFN group and NAs addon Peg-IFN group at 72 weeks were 45.5% (25/55) and 32.9% (23/70) (P=0.151). No patient got HBsAg clearance or seroconversion in NAs group and untreated group. Furthermore, the receiver operator curve showed baseline HBsAg <72IU/ml, the declination of HBsAg more than 80% and 98% from baseline to 12 and 24 weeks provide good prediction for HBsAg clearance. Meanwhile, 77% patients with baseline HBsAg<100IU/ml got clinical cure at 48 weeks. Conclusion: Peg-IFNα-2b results in high rate of HBsAg clearance and seroconversion both in IHCs and NA-experienced patients, especially, for those patients who HBsAg below 100 IU/ml.